Implementasi pendidikan berbasis luaran untuk meningkatkan kompetensi pedagogik mahasiswa PGMI - Armiya Sayidatun Nafi'ah; Sukiman Sukiman (Universitas Pendidikan Indonesia, 2026)
Outcome-Based Education (OBE) has become an important approach in higher education to produce graduates with measurable competencies through student-centered learning. However, studies examining its implementation in improving the pedagogical competence of prospective elementary Islamic school teachers remain limited, particularly in private Islamic higher education institutions. This study aimed to analyze the implementation of the OBE curriculum in improving the pedagogical competence of students in the Primary School Teacher Education (PGMI) Program at IAI Khozinatul 'Ulum Blora. A qualitative case study was employed using observations, interviews, and document analysis. Data were analyzed through data reduction, data display, and conclusion drawing, while source and technique triangulation ensured the credibility of the data. The findings revealed that OBE implementation strengthened students' pedagogical competence through outcome-based instructional planning, student-centered learning, and authentic assessment, enabling students to develop competencies in lesson planning, classroom management, assessment, and understanding student characteristics. The study concludes that successful OBE implementation depends not only on achieving learning outcomes administratively but also on providing authentic learning experiences that foster prospective teachers' pedagogical competence.